Health care-associated infections and associated factors among adult patients admitted to intensive care units of selected public hospitals, Addis Ababa, Ethiopia - Wondimagegn Genaneh; Migbar Sibhat; Tesfaye Techane; Tesfaye Girma Legesse (Elsevier, 2023)
Background: Healthcare-associated infections are illnesses acquired from an infectious agent or toxins after 48 h of admission. In low- and middle-income countries healthcare-associated infection is as high as 88.9%. Moreover, studies realized the intensive care unit is a prominent place for acquiring infections; whereas, there are scarce of studies, especially at an intensive care unit in Ethiopia. Method: An institutional-based retrospective cross-sectional study design was used to determine the prevalence and associated factors of healthcare-associated infections among 404 adult patients admitted to the intensive care unit from September 11, 2017, to September 11, 2019, GC at St. Paul's Hospital Millennium Medical College and Addis Ababa Burn Emergency and Trauma Hospital Addis Ababa, Ethiopia in 2020. Variables that had a value of P ≤ 0.25 on bi-variable analysis were directly forwarded to be analyzed by multivariable analysis. P-values < 0.05 are considered statistically significant at a 95% confidence interval using SPSS version 20 software. Result: A total of 199(50.9%) study participants have had at least one healthcare-associated infection. Urinary tract infection 94(47.2%); and hospital-acquired pneumonia 89 (44.7%) were among the common infections. Of all healthcare-associated infections, 112(56.3%) were devise-associated infections. Among patients admitted to intensive care units for cases of respiratory failure, traumatic brain injury, and acute kidney injury, about 100(50.2%), 39 (19.6%), and 59(29.6%) of them have developed a healthcare-associated infection respectively. Length of hospital stay (AOR = 1.05), stroke (AOR = 4.34), central vascular catheterization (AOR = 3.41), endotracheal intubation (AOR = 3.6), antibiotic prophylaxis (AOR = 12), and blood transfusion (AOR = 0.49) determined to have a significant association with healthcare-associated infections. Conclusion: Healthcare-associated infection is a highly prevalent problem among intensive care unit-admitted patients in the study area.